Pengoperasian Penalaran Bayāni dalam Alqur’an (Analisis Metode Amar dalam Perintah Shalat) - Hana, Yusro (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2022)
In essence, fiqh law is an extract from the arguments of the Al-Quran and Hadith which are the main priority sources of Islamic law and are carried out by the method of reasoning in ushul fiqh. The need for the operation of ushul fikh rules is felt to be very important because the problems that arise in society arise and grow in various ways. Therefore, this paper wants to examine how the pattern of bayani reasoning in ushul fiqh? and How is the operation of ushuliyyah rules in fiqh cases? This research is in the qualitative realm which is more directed to conceptual ideas based on literature analysis (Library Research). The result of this study is that bayāni reasoning is a pattern of reasoning that is based on linguistic rules or on the meanings of pronunciation to find out the arguments that are 'amm and hash, muthlaq-muqayyad, nasikh-mansukh, amr, nahy, musytarak, majaz, essence, and others. According to majority ulema, dalalah amar muthlaq is essentially obligatory. unless there is an indication that turns it to other than obligatory, then amar is interpreted in accordance with the demands of the indication. According to majority ulema, amar muthlaq does not refer to repetition and haste to carry out actions. Whereas nahi muthlaq refers to repetition and haste to leave an act.